International Benchmarking and Determinants of Mathematics Achievement in Two Indian States - Wu, Kin Bing (2012)
Evidence from cross-country studies suggests that the sustainability of India's rapid economic growth will be conditioned by the quality of its education. This paper analyzed a 2005 World Bank-sponsored survey of grade nine students in the states of Rajasthan and Orissa. The survey used internationally comparable items from the 1999 Trends of Mathematics Study to provide the first international benchmark for education quality in India for three decades. The study finds that only 15% and 25% of students in Rajasthan and Orissa, respectively, have achieved the expected international average of these items. The study further shows that increasing students' opportunity to learn through better pedagogical practices and enhanced schooling experience can increase performance, while mitigating between-school inequality, and reducing the achievement gap between boys and girls, holding other factors constant.